Undergraduates students' learning experience on the impact of online learning during pandemic - Omar, Muhd Khaizer; Hassan, Monzurul; Mohamad Arsad, Nurazidawati; Ismail, Normala; Jamaluddin, Rahimah; Jusoh, Rosnani (Scientific Research Publishing, 2021)
The Coronavirus pandemic has shifted the norms and standard practices in the education setting and significantly impacted higher education. This unprecedented situation has created uncertainties in students’ learning and the instructional process in general. Hence, the aim of this study was to explore the learning experience of students during this Covid-19 pandemic. A total of 68 informants among undergraduate and postgraduate students from Universiti Putra Malaysia (UPM) participated in this case study. They were asked to share their learning experiences via open-ended questions that were distributed via an online data collection platform called “JotForm”. The narrative responses were analysed using thematic analysis. Five themes emerged from the narrative analysis: 1) Institutional support, 2) emotional engagement, 3) cognitive engagement, 4) behavioural engagement, and 5) students’ satisfaction. The results: 1) amplified the urgent call for a reliable internet connection to facilitate the online instruction process, 2) proved the readiness of lecturers to adopt online teaching, 3) showed the need to create a conducive online learning environment, and 4) indicated the need to foster learning satisfaction. The deadly pandemic has continued to spread unabated all over the world, but education at all levels must continue. Therefore, appropriate measures must be put in place to facilitate the instruction process for the whole community of learners.